Analysis of Judges' Considerations in Religious Court Decision Number 1332/PDT.G/2020/PA.BTL Concerning Default in Business Contracts - Sudiyana; Devi Andani; Fatma Faizati (Journal of Private and Commercial Law, 2025)
This research aims to analyze and find out the legal considerations of the panel of judges in the decision of case Number 1332/Pdt.G/2020/PA.Btl) for the parties of the istishna' sale and purchase agreement which does not stipulate a delivery time limit. This research is normative legal research, which emphasizes the study of statutory norms, principles and principles of positive law, positive legal theory and basically legislative, conceptual and case approaches. In case decision Number 1332/Pdt.G/2020/PA.Btl., the panel of judges considered that the preliminary sale and purchase agreement was declared valid and binding on both parties because it had fulfilled the legal requirements of the agreement. As a legal consequence, the agreement remains valid and binding on both parties. Both parties still have the obligation to complete their achievements in good faith.